Geweld macht en onmacht. - Arendt, Hannah 1906-1975; Mok, Maurits (Utrecht Spectrum, 1970)
Philosophical essay on violence and its different aspects and consequences in the society. Definitions of violence, power, force, strength, authority. Character and origins of violence.